STRENGTHENING BLUE ECONOMY MANAGEMENT BASED ON PENTHA HELIX COLLABORATION IN ORDER TO REALIZE THE WELFARE OF THE PEOPLE IN INDONESIA - Agustiawarman; K.P. Suharyono S. Hadiningrat (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The potential of Indonesia's marine wealth is very large but the utilization is only about 7 percent of the Gross Domestic Product (GDP) since it was proclaimed as the World Maritime Axis (PMD) in 2014, so it is necessary to strengthen blue econony management efforts based on pentha helix collaboration in order to realize people's welfare. With a descriptive qualitative research design and combined with SWOT analysis, the results show that the strengths are: a) The regulation of the marine sector already exists (Law No.32 of 2014 concerning Maritime Affairs along with its derivative regulations); b) Sovereignty over Indonesia's sea territory based on the 1957 Djuanda Declaration; c) Recognition of other countries over Indonesia's sea territory according to the Convention on International Law of the Sea - United Nations (UNCLOS 1982); d) The existence of four basic national consensus namely Pancasila, 1945 Constitution, NKRI and Unity in Diversity; and e) Indonesia is declared as the World maritime Axis. The weaknesses are: a) Maritime technology support is still limited; b) Maritime human resources are still lacking both quantity and quality; c) Sectoral ego is still high; d) Illegal Fishing is rampant and e) Prone to threats from abroad. The opportunities are very potential, among others: a) Utilization of demographic bonuses as HR Talents; b) Preparation of the Golden Indonesia in 2045 c) to become an Advanced Indonesia; d) Pentha Helix partnership cooperation; and e) Utilization of digital-based maritime technology. The challenges include: a) Geographical conditions that are in the cross position of world trade; b) The vastness of Indonesia's sea area has the potential to be a threat. The vastness of Indonesia's sea area is a potential threat; c) Indonesia as a center of gravity for other countries; d) The escalation of the South China Sea conflict has widened to the Indopacific; and e) The uncertain global geopolitical dynamics. Therefore, efforts are made to strengthen blue economic management based on pentha helix collaboration in order to realize the welfare of the people in Indonesia, among others, through joint forums to discuss various issues to find the best solution so that it is effective, efficient, fast and precise. In this case, the Coordinating Ministry for Maritime Affairs and Investment is the leading sector in managing Indonesia's seas for the benefit of all the people, the nation and the Unitary State of the Republic of Indonesia. Based on the above conclusions, it is recommended to: a) The central government, in this case the Coordinating Ministry for Maritime Affairs and investment, must really focus on being the leading sector in managing the blue economy in Indonesia based on the pentha helix which involves elements of government, universities, industry, society and the media.